Serb Returnees in Croatia - the Question of Return Sustainability - Mesić, Milan, sociolog (Array, 2010)
The authors report on representative field research dealing with ethnic Serb returnees to Croatia. The total sample consisted of 1, 500 randomly chosen persons from a population of 120, 000 officially registered Serb returnees to Croatia. The main questionnaire was answered by 403 respondents. Drawing on references relating to the concept of sustainability, they further develop it through differentiation of seven sustainability aspects or dimensions: safety ; socio-demographic structure of returnees ; socio-economic conditions of return ; refugee experiences ; citizenship and minority rights ; and subjective perceptions of sustainability. According to field findings, between 35 and 45 per cent of the registered returnees reside permanently at the addresses they reported upon return, and an additional 3, 5 per cent moved to other locations within Croatia. The findings and conceptualization suggest the need for a differentiated approach to a returnee body to better understand the complexity of a return. First, we have to distinguish among refugees potential returnees from non-returnees (political and economic ones). Returnees themselves can then be grouped into several types: I) unconditional permanent ; II) conditional permanent ; III) semi-returnees or trans-national ; IV) non-formal and V) formal or quasi-returnees.